2003
DOI: 10.1167/iovs.02-0705
|View full text |Cite
|
Sign up to set email alerts
|

Centripetal Movement of Corneal Epithelial Cells in the Normal Adult Mouse

Abstract: Corneal epithelium of adult GFP mice exhibits a pattern of GFP expression that is suitable for studying cell movement in the normal cornea. Epithelial cells at the basal or suprabasal layers move centripetally in these mice at an average rate of 26 micro m/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 25 publications
7
102
3
Order By: Relevance
“…For mouse corneas, the rate of centripetal movement has been estimated as 11-26 µm/d using three different approaches involving direct observations of labelled cells. Corneal epithelial cells labelled with India ink moved 17 µm/d over 7 d [62] , patches of brightly fluorescent cells moved 26 µm/d over 7 wk in mosaic GFP transgenic mice [63] and fluorescent clones of cells extended 11 µm/d over 12 wk in K14-CreERT2;R26R-confetti transgenic mice (from 9 to 21 wk after tamoxifen-activation of the reporter transgene) [64] . Furthermore, the evidence from the mosaic GFP transgenic mice [63] and tamoxifen-activated reporter transgenic mice [64] demonstrated that the same clonal lineage of cells moved across the full radius from the periphery to the centre.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mouse corneas, the rate of centripetal movement has been estimated as 11-26 µm/d using three different approaches involving direct observations of labelled cells. Corneal epithelial cells labelled with India ink moved 17 µm/d over 7 d [62] , patches of brightly fluorescent cells moved 26 µm/d over 7 wk in mosaic GFP transgenic mice [63] and fluorescent clones of cells extended 11 µm/d over 12 wk in K14-CreERT2;R26R-confetti transgenic mice (from 9 to 21 wk after tamoxifen-activation of the reporter transgene) [64] . Furthermore, the evidence from the mosaic GFP transgenic mice [63] and tamoxifen-activated reporter transgenic mice [64] demonstrated that the same clonal lineage of cells moved across the full radius from the periphery to the centre.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
“…When Majo et al [1] proposed the CESC cell hypothesis they also proposed that the corneal and conjunctival epithelia continuously expand towards the limbus, which they described as a zone of equilibrium, so any movement in the corneal epithelium was predicted to be centrifugal. This is inconsistent both with the absence of movement in the conjunctiva [62,65] and the convincing, direct evidence that movement of corneal epithelial cells is centripetal not centrifugal [62][63][64] . The evidence for centripetal cell movement in the corneal epithelium is inconsistent with the CESC hypothesis as originally proposed [1] but there is no need to link the stem cell location and movement aspects of the original CESC hypothesis.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
“…Central epithelial abrasion without stromal injury results in three general phases of healing. 22,24,30,31 The initial lag phase lasts ϳ6 hours. The migration phase in which epithelial cells (basal and suprabasal) crawl over the provisional matrix on the stromal surface to close the wound lasts ϳ24 hours.…”
Section: Corneal Epithelial Healingmentioning
confidence: 99%
“…The limbus harbours the stem cells of the corneal epithelium [10,[12][13][14][15][16][17][18]. Limbal stem cell identification and molecular characterization have been reviewed [19,20], but not in relation to tissue regeneration.…”
Section: G Pellegrini Et Almentioning
confidence: 99%
“…Relatively undifferentiated and slow-cycling epithelial cells have been found in the limbal basal layer but not in the central cornea [12][13][14]. Cell migration from the limbus towards a wounded cornea [14,15,20,[23][24][25][26] and mathematical analyses of the maintenance of the corneal epithelial cell mass [27] strengthened the X, Y, Z hypothesis of corneal epithelial preservation by proliferating and migrating limbal stem cells [28]. Surgical removal of the limbus initially results in corneal healing [29] but subsequent corneal mechanical wounds result in a progressive vascularization and recurrent erosions of the cornea, confirming that the corneal epithelium has a limited regenerative capacity [29].…”
Section: Location Of Human Corneal Stem Cellsmentioning
confidence: 99%